The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.nbscr.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation impairs recognition of specific emotions

Abstract: Emotional processing is particularly sensitive to sleep deprivation, but research on the topic has been limited and prior studies have generally evaluated only a circumscribed subset of emotion categories. Here, we evaluated the effects of one night of sleep deprivation and a night of subsequent recovery sleep on the ability to identify the six most widely agreed upon basic emotion categories (happiness, surprise, fear, sadness, disgust, anger). Healthy adults (29 males; 25 females) classified a series of 120 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 29 publications
3
40
1
2
Order By: Relevance
“…By engaging in TL, a leader changes followers' cognitions, emotions and behaviour from a self‐oriented perspective into a community orientation by personal example and inspiring interactions (Bass and Riggio, ). This requires access to a broad spectrum of sleep‐vulnerable personal resources (Byrne et al ., ; Killgore et al ., ; Olsen et al ., ), such as positive affect (Rubin et al ., ), and hope and optimism (Peterson et al ., ). According to Hobfoll (), a leader depleted of such resources will take a more defensive posture, conversely to proactive TL.…”
Section: Introductionmentioning
confidence: 99%
“…By engaging in TL, a leader changes followers' cognitions, emotions and behaviour from a self‐oriented perspective into a community orientation by personal example and inspiring interactions (Bass and Riggio, ). This requires access to a broad spectrum of sleep‐vulnerable personal resources (Byrne et al ., ; Killgore et al ., ; Olsen et al ., ), such as positive affect (Rubin et al ., ), and hope and optimism (Peterson et al ., ). According to Hobfoll (), a leader depleted of such resources will take a more defensive posture, conversely to proactive TL.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the findings by Kyle and colleagues and the current findings of a relationship between beta EEG power during sleep and altered salience processing in insomnia, further research should be conducted on the interplay between hyperarousal during sleep and both affective disturbance and salience processing during wake. It is also suggested that poor sleep in insomnia may lead to performance deficits in emotional face perception, similarly to that which has been reported after nights of experimental sleep deprivation [82][83][84][85], which might also contribute to socioemotional impairment. The extent and type of emotional impairment after nights of poor sleep and hyperarousal in insomnia requires further investigation.…”
Section: Sleep and Emotion Processing Group Differencesmentioning
confidence: 54%
“…For example, sleep duration was found to be associated with peer acceptance and social engagement, two components of peer social competence (Vaughn et al, 2015). Sleep disturbance can lead to impaired social interactions (Gilbert et al, 2015) and reduce self-expression in social interactions (Condén et al, 2013) and has the potential to reduce the accuracy of identifying facial expressions of happiness and sadness (Crönlein et al, 2016;Killgore et al, 2017). The effect of sleep deprivation on facial emotion identification was also confirmed by the results of resting state EEG studies.…”
Section: Introductionmentioning
confidence: 83%